Kampanye Literasi Media Digital Melalui Iklan Layanan Masyarakat Google Indonesia #RecheckSebelumKegocek - Nabilla Anasty Fahzaria; Sarah Annisa Fadhila (Jurnal Inovasi Komunikasi, 2025)
Abstract. Ahead of the 2024 Indonesian Election, hoaxes based on manipulated visual content are rampant in the digital ecosystem. Google Indonesia launched a public service announcement campaign #RecheckBeforeKegocek to improve digital media literacy. This study analysed the advertisement using a qualitative approach with Teun A. van Dijk's Critical Discourse Analysis method, which dissects the text structure (super macro, superstructure, microstructure) and efforts to develop digital media literacy competencies ahead of the election. This study focuses on the research object, namely a public service announcement created by Google Indonesia entitled #RecheckBeforeKegocek, which was posted on the Instagram account @googleindonesia on October 12, 2023, and displayed as an advertisement on YouTube with a duration of 1 minute 29 seconds. The data collection methods used in this study were documentation, observation, and recording, with data analysis techniques referring to the Miles & Huberman approach. The results show that this advertisement functions as a social promotion tool to improve digital media literacy, especially in recognizing manipulative visual content. This advertising discourse is unique, opening up opportunities for further exploration of digital media literacy education within families and educational institutions, making it relevant for strengthening public awareness of hoaxes ahead of Indonesian elections.